THE USE OF BOTULINUM TOXIN IN THE TREATMENT OF MIGRAINE - Julia Surowaniec; Dawid Nowicki; Małgorzata Muszyńska; Katarzyna Karaś; Sylwia Mroszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Migraine is a chronic neurological disorder marked by recurrent moderate to severe headaches with symptoms such as nausea, photophobia, and phonophobia. Chronic migraine, occurring on 15 or more days per month for over three months, significantly impairs daily functioning and creates a substantial health burden. Botulinum toxin type A (BoNT-A) is an effective preventive option for patients who do not respond to standard treatments. Aim of the study: The aim of this review is to summarize current evidence on the mechanism of action, clinical efficacy, safety profile, and practical use of botulinum toxin type A in the prevention of chronic migraine. Materials and methods: A literature search was mostly performed in PubMed and Google Scholar for studies published between 2015 and 2025, using the keywords: migraine, chronic migraine, botulinum toxin, onabotulinumtoxinA, PREEMPT trials, CGRP. Priority was given to randomized controlled trials, long-term observational studies, clinical guidelines, and mechanistic research. Discussion: OnabotulinumtoxinA (BoNT-A) is a well-established preventive treatment for chronic migraine supported by evidence from the PREEMPT trials and long-term studies such as COMPEL. BoNT-A significantly reduces headaches, improves quality of life and decreases disability with benefits sustained over multiple treatment cycles. Its mechanism blocking the release of CGRP, substance P, and glutamate from sensory nerves and modulating nociceptive receptors targets both peripheral and central sensitization, which distinguishes it from traditional oral medication. Injection protocols vary worldwide. The PREEMPT paradigm is evidence-based and standardized, while alternative approaches, such as the Saudi 5/20/100 protocol, offer lower doses and fewer injections but lack of large-scale validation. The safety profile is generally positive. Following recommended dosing intervals minimizes the risk of neutralizing antibodies. Emerging CGRP-targeting therapies provide additional options, and early data suggest potential benefits of combination therapy for refractory cases. Economic analyses indicate that despite higher upfront costs, BoNT-A reduces healthcare use and disability, making it cost-effective in the long term. Future research should focus on identifying predictors of response, optimizing injection protocols, and evaluating combination strategies with biologics. Results: Evidence from large randomized trials (PREEMPT 1 and 2) demonstrates that BoNT-A significantly reduces the number of headache days, improves quality of life, and decreases disability in patients with chronic migraine. Long-term studies show sustained benefits over multiple treatment cycles with a favorable safety profile. BoNT-A reduces peripheral and central sensitization by inhibiting the release of pain-related neuropeptides and modulating sensory nerve activity. Conclusion: OnabotulinumtoxinA is an effective and well-tolerated preventive treatment for chronic migraine. Standardized injection protocols and appropriate patient selection optimize therapeutic outcomes. Further research is needed to identify predictors of treatment response and to explore the potential of combination therapy with CGRP (calcitonin gene-related peptide)-targeting agents.